Handbook of child and adolescent anxiety disorders - McKay, Dean.; Storch, Eric A.; SpringerLink (Online service). (New York Springer, 2011)
Is it school refusal or separation anxiety disorder? Can preschoolers have panic attacks? Does food neophobia really exist? For readers seeking ways to improve assessment, case conceptualization, or treatment plans as well as a more general understanding of anxiety disorders among children, the Handbook of Child and Adolescent Anxiety Disorders addresses these and many other complex issues. A straightforward companion to the diagnostic manuals, this volume crosses theoretical boundaries to describe in depth the wide range of children?s anxiety disorders and to explain the developmental nuances that separate them from their adult analogues. Coverage includes: Diagnostic and etiological models of children's anxiety disorders (i.e., genetic, cognitive-behavioral, taxonomic, neuropsychological, dimensional). Differential diagnosis guidelines for generalized anxiety disorder (GAD), phobic conditions, obsessive-compulsive disorder (OCD), and posttraumatic stress disorder (PTSD) in youth. Ancillary factors in child and adolescent anxiety (e.g., personality, temperament, parenting issues, and comorbid conditions). Psychological, pharmacological, and combined treatments for childhood anxiety disorders. Special populations and emerging areas of interest, including anxiety disorders in the contexts of chronic health problems and developmental disabilities. The Handbook of Child and Adolescent Anxiety Disorders is a must-have reference for researchers, clinicians, and graduate students in psychology, psychiatry, social work and counseling as well as allied professionals in hospitals, community mental health centers, schools, and private practice.
Dedication -- About the Editors -- List of Contributors -- Section I: Foundations in Child & Adolescent Anxiety -- Classification of Child & Adolescent Anxiety Disorders -- Issues in Differential Diagnosis: Phobias and Phobic Conditions -- Issues in Differential Diagnosis: Considering Generalized Anxiety Disorders, Obsessive-Compulsive Disorder, and Posttraumatic Stress Disorder -- Section II:  Diagnostic Components in Child/Adolescent Anxiety Disorders -- Cognitive Behavioral Models of Phobias and Pervasive Anxiety -- Genetics of Childhood and Adolescent Anxiety -- Neuropsychological Considerations in Child and Adolescent Anxiety -- Empirical Approaches to the Study of Latent Structure and Classification of Child and Adolescent Anxiety Psychopathology -- Dimensional Diagnosis of Anxiety in Youth -- Section III: Ancillary Components of Child & Adolescent Anxiety -- Differential Diagnosis and Comorbid ADHD in Childhood Anxiety -- Comorbid and Secondary Depression -- The Role of Disgust in Childhood Anxiety Disorders -- Emotion Regulation in Childhood Anxiety -- Emergent Personality Disorders among Adolescents with Anxiety Disorders -- Temperament and Anxiety Disorders -- Parenting and Child Anxiety Disorders -- Section IV: Psychological and Pharmacological Treatments of Child/Adolescent Anxiety Disorders -- Specific Phobias -- Separation Anxiety Disorder -- Generalized Anxiety Disorder -- Selective Mutism -- Social Anxiety -- Pediatric Posttraumatic Stress Disorder -- Obsessive-Compulsive Disorder -- Pharmacological Treatment for Phobias and Anxiety Disorders -- Pharmacologic Approaches to Medication-Resistant Anxiety in Children and Adolescents -- Psychopharmacological Treatment of Anxiety in Adolescents with Comorbid Substance Abuse -- Combined Psychological and Pharmacological Treatment of Pediatric Anxiety Disorders -- Section V: Special Populations and Additional Treatment Elements -- Parent Training for Childhood Anxiety -- School-Based Interventions for Anxiety in Youth -- Phobias and Anxiety-Related Problems in Mental Retardation and Developmental Disabilities -- Food Neophobia in Children: Misnomer, Anxious Arousal, or Other Emotional Avoidance? -- Social Disability and Impairment in Childhood Anxiety -- Anxiety Disorders in Children with Chronic Health Problems -- Immune and Endocrine Function in Child and Adolescent Obsessive Compulsive Disorder.
Electronic reproduction.
Keywords: Anxiety disorders; Adolescent; Child; Differential diagnosis; Electronic books